The illusion of no control: management control systems facilitating autonomous motivation in university research. (26th November 2014) - Sutton, Nicole C.; Brown, David A.
Abstract: Autonomous motivation, a fundamental factor influencing research success, can be undermined when people feel pressured, managed or controlled. So how do universities – which are under increasing external pressure to manage research activities to produce outcomes – exert management control without threatening the autonomous motivation of their researchers? We address this question through an exploratory case study of the management control systems used in two university faculties. Our results confirm the importance of autonomous motivation in driving researchers' activity and show how incentives, performance evaluation and cultural–administrative structures can be designed to not only preserve, but also enhance and leverage this motivation.